(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Text tasks are very important in elementary grades. Problems are very useful for the development and thinking of students. Any questions that are interesting and engage the student in thought will have a more positive impact on their brain activity. For elementary school students, not too difficult one- or two-step tasks are recommended. Through them, the horizons of thinking expand and serve as the basis for complex issues that will be worked on in the next stages. To complete any complex examples and problems, you must first be able to work with simple looking examples and problems